GNAS Spectrum of Disorders - DEMİRCİOĞLU, SERAP (SPRINGER, 2015)
The GNAS complex locus encodes the alpha-subunit of the stimulatory G protein (Gs alpha), a ubiquitous signaling protein mediating the actions of many hormones, neurotransmitters, and paracrine/autocrine factors via generation of the second messenger cAMP. GNAS gives rise to other gene products, most of which exhibit exclusively monoallelic expression. In contrast, Gs alpha is expressed biallelically in most tissues; however, paternal Gs alpha expression is silenced in a small number of tissues through as-yet-poorly understood mechanisms that involve differential methylation within GNAS. Gs alpha-coding GNAS mutations that lead to diminished Gs alpha expression and/or function result in Albright's hereditary osteodystrophy (AHO) with or without hormone resistance, i.e., pseudohypoparathyroidism type-Ia/Ic and pseudo-pseudohypoparathyroidism, respectively. Microdeletions that alter GNAS methylation and, thereby, diminish Gs alpha expression in tissues in which the paternal Gs alpha allele is normally silenced also cause hormone resistance, which occurs typically in the absence of AHO, a disorder termed pseudohypoparathyroidism type-Ib. Mutations of GNAS that cause constitutive Gs alpha signaling are found in patients with McCune-Albright syndrome, fibrous dysplasia of bone, and different endocrine and non-endocrine tumors. Clinical features of these diseases depend significantly on the parental allelic origin of the GNAS mutation, reflecting the tissue-specific paternal Gs alpha silencing. In this article, we review the pathogenesis and the phenotypes of these human diseases.
Keywords: GNAS; Pseudohypoparathyroidism; Gs alpha; Alpha-subunit of the stimulatory G protein; PSEUDOHYPOPARATHYROIDISM-TYPE-IB; XL-ALPHA-S; MCCUNE-ALBRIGHT-SYNDROME; STIMULATORY G-PROTEIN; PROGRESSIVE OSSEOUS HETEROPLASIA; IMPRINTING CONTROL ELEMENT; IN-VITRO FERTILIZATION; GS-ALPHA; FIBROUS DYSPLASIA; AUTOSOMAL-DOMINANT